Morphological, anatomic and karyotypic characteristics of Peliosanthes teta Andrew - Phichai Chaikla (2018)
Peliosanthes teta Andrew, domesticated indigenous vegetable, obtains high potential of commercial production. Huai Hong Khrai Royal Development Study Centre, Doi Saket, Chiang Mai carried out surveys and collections of the plants in the areas of the Upper-North of Thailand. The plants were then grown in the collection plots inside the centre. Samples of 72 accessions were taken for characterization, morphologically and anatomically. Plant parts studies included roots, stems, leaves and flowers. The chromosomes were also investigated. Studies showed that the plant accessions shared similar morphological and anatomic structures. Chromosome number checked from 16 accessions were the same, that is, 2n = 54. Karyotypic formula was L 2m + L 2a + L 2sm + M 2a + S 4a + S 36m + S 6sm. © 2011 Academic Journals.